Analysis of the Effectiveness of the Free Nutritious Meals Program Viewed from the Case of Unfit-for-Consumption Food in East Lombok. - Irawan, Danu; Rahma, Dinda Suci Lovea; Cahyani, Maulidiya Gita; Nirmalasari, Puja (Jurnal Penelitian Pendidikan, 2025)
Free Nutritious Meals Program (MBG) is a national government initiative launched in 2025 aimed at improving student nutrition and enhancing the quality of the teaching-learning process. However, its implementation in the field still faces several challenges. This study aims to evaluate the success of the MBG program and reveal the issues that arise through a case analysis of findings of unsafe food consumption at SDN 2 Sandubaya, East Lombok. Research data was collected from official documents, literature reviews, and media reports. The findings indicate deficiencies in kitchen hygiene, quality monitoring, and food distribution management, leading to biological contamination such as the presence of maggots in student meals. This situation affects the decline in student health, sense of safety, and parental trust in the program. Analysis using Maslow's Hierarchy of Needs theory emphasizes that the inability to fulfill basic physiological needs and a sense of security can hinder students' readiness to learn. This study recommends the implementation of rigorous sanitation standards, layered supervision, improvement of food provider competencies, and regular evaluations to ensure the MBG program runs efficiently and contributes to improving educational standards in Indonesia.s employed. Please identify at least three keywords through which your research is most easily identified.